Pengaruh Self-Efficacy Pada Kecemasan Tokoh Utama Dalam Novel A Untuk Amanda Karya Annisa Ihsani - Rr Aisha Elok Paraswati; Anastasia Adelia Ayu Hartana; Eva Dwi Kurniawan (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to analyze self-efficacy regarding the anxiety of the main character in the novel A for Amanda by Annisa Ihsani. Using four sources of self-efficacy with the psychological approach of Albert Bandura's social cognitive theory. The research method used is a qualitative descriptive method. Data collection was carried out using note-taking techniques and literature study. The results of this research reveal the self-efficacy of the main character (Amanda) through four sources of self-efficacy, namely experience of success (enactive attainment), indirect experience (vicarious experience), verbal persuasion (verbal persuasion), and physiological state (physiological state). These sources of self-efficacy provide conclusions regarding the efficacy of the main character (Amanda).